Copper-Catalyzed 6-endo-dig O-Cyclization of 2-(But-3-en-1-yn-1-yl)benzamide - Wang, Rui-Xiang; Fang, Zhuang; Qiu, Guanyinsheng; Xie, Wenlin; Liu, Jin-Biao (Synthesis, 2019)
The copper-catalyzed synthesis of 3-vinylisocoumarin-1-imine is reported. The transformation proceeds smoothly with good yields in THF and the regioselectivity was determined by a O-nucleophilic 6-endo cyclization. Studies on the mechanism indicate that copper trifluoroacetate serves as a Lewis acid, and the use of vinyl-connected 2-alkynylbenzamide is important for this O-nucleophilic 6-endo cyclization.
Keywords: copper catalysis; O-nucleophilic 6-endo cyclization; Lewis acid; vinyl-connected 2-alkynylbenzamide; isocoumarin